The Annexation of the Transvaal in 1877: The First Boer Reactions - Leśniewski, Michał (Werkwinkel, 2017)
In April 1877 The South African Republic was annexed by the British Empire. This was a part of a wider scheme to unify the sub-continent under the British rule. The story is well known. Many works deals with the motives of Lord Carnarvon and other British decision-makers. Much less deals with the question of immediate Boer reaction, or to be exact, the reasons behind their inaction. This article deals with this problem. Tries to evaluate the attitudes of both, the British and the Boers, and to show why the Transvaal Boers mostly ignored the annexation declaration? This text is just an excursion into field which demands much wider and more detailed studies.